Advancements in the Application of the Fenton Reaction in the Cancer Microenvironment - Rile Ou; Gerile Aodeng; Jun Ai (MDPI AG, 2023)
Cancer is a complex and multifaceted disease that continues to be a global health challenge. It exerts a tremendous burden on individuals, families, healthcare systems, and society as a whole. To mitigate the impact of cancer, concerted efforts and collaboration on a global scale are essential. This includes strengthening preventive measures, promoting early detection, and advancing effective treatment strategies. In the field of cancer treatment, researchers and clinicians are constantly seeking new approaches and technologies to improve therapeutic outcomes and minimize adverse effects. One promising avenue of investigation is the utilization of the Fenton reaction, a chemical process that involves the generation of highly reactive hydroxyl radicals (·OH) through the interaction of hydrogen peroxide (H2O2) with ferrous ions (Fe2+). The generated ·OH radicals possess strong oxidative properties, which can lead to the selective destruction of cancer cells. In recent years, researchers have successfully introduced the Fenton reaction into the cancer microenvironment through the application of nanotechnology, such as polymer nanoparticles and light-responsive nanoparticles. This article reviews the progress of the application of the Fenton reaction, catalyzed by polymer nanoparticles and light-responsive nanoparticles, in the cancer microenvironment, as well as the potential applications and future development directions of the Fenton reaction in the field of tumor treatment.